First Photographic Record of Gharial (Gavialis gangeticus) from Kaziranga Tiger Reserve, India - Sharma, Tridip; Das, Sunit Kr.; Bora, Pranab J.; Sarmah, Anupam; Chanchani, Pranav; Thatte, Prachi; Sharma, Rabin; Gogoi, Ramesh Kr.; Baishya, Kanak (Indian Forester, 2023)
No Abstract.